Implementation of the Playing, Telling Stories, and Singing Method in Increasing Student Learning Motivation in the SKI Subject - Hani Siti Nuraeni; Masripah Masripah; Yufi Muhamad Nasruloh (al-Afkar, Journal For Islamic Studies, 2026)
Education plays a crucial role in shaping the character, knowledge, and civilization of the nation, including the teaching of Islamic Cultural History (SKI), which serves to instill Islamic values and character in students. However, in practice, SKI learning is often considered uninteresting, resulting in low student motivation. This study aims to determine the effect of implementing the BCM (Playing, Telling, and Singing) method on improving student motivation in SKI in sixth-grade students at MI Attamimi. This study used a quantitative approach with an experimental design using a One Group Pretest–Posttest. Forty students participated in the study. Data collection techniques included observation and documentation, while data analysis included validity, reliability, normality, homogeneity, independent t-tests, and the N-Gain test using SPSS version 27. The results showed that the research instrument had very high reliability, with a Cronbach's Alpha value of 0.922. The data were normally distributed and homogeneous. The N-Gain test showed an average value of 81.79, which is in the high category. These findings indicate that the implementation of the BCM method significantly increases students' learning motivation. Therefore, the BCM method is effective as an alternative to Islamic Studies (IS) learning that is more active, enjoyable, and meaningful. This research contributes to providing an alternative innovative learning method through the application of the BCM method (Playing, Telling, and Singing) to increase students' learning motivation in the subject of Islamic Cultural History.